Monitoring Water Turbidity in the Chiang Rai Reach of the Mekong River Using Sentinel-2 NDTI - Nontapon, Jurawan; Kummuang, Phailin; Srihanu, Neti; Bhomi, Arun Kumar; Shrestha, Rabi; Poudyal, Rabina; Bhurtyal, Umesh; Pant, Pragya; kaewplang, siwa (RMUTL Engineering Journal, 2025)
The Mekong River plays a vital role in regional ecology, food security, and water governance, yet turbidity monitoring in its upper reaches remains limited. The Chiang Rai sector, located at the first upstream entry point of the Lower Mekong Basin, functions as a sediment and flow gateway to downstream countries; however, no systematic satellite-based turbidity assessment has previously been conducted for this area. This study addresses this gap by applying the Normalized Difference Turbidity Index (NDTI) derived from Sentinel-2 MSI imagery to investigate spatial and seasonal turbidity dynamics from 2019 to 2024. Multi-temporal satellite datasets were processed using Google Earth Engine and integrated with monthly rainfall (TerraClimate) and water surface area extracted using the Modified Normalized Difference Water Index (MNDWI). Results revealed a clear monsoonal pattern, with turbidity peaking between June and September and declining during the dry season (November-April). Regression analysis showed a moderate correlation between rainfall and turbidity (R² = 0.37), while a stronger association with water surface area (R² = 0.514) indicates the dominant influence of hydromorphological processes such as sediment resuspension and floodplain connectivity. Although the absence of field-based turbidity measurements represents a key limitation, the findings demonstrate the potential of Sentinel-2-based NDTI as a cost-efficient monitoring tool in data-scarce transboundary basins. This study provides the first satellite-derived turbidity baseline for the northern Mekong and offers a practical framework to support basin-wide water-quality monitoring and policy decision-making under increasing hydropower regulation and climate variability.